Estudo comparativo da estrutura da comunidade bentônica de duas represas com diferenças no grau de eutrofização - Pamplin, Paulo Augusto Zaitune (2004)
The present study aimed to determine and compare the structure of benthic invertebrates community in two reservoirs strongly differing in relation to trophic state. The reservoirs studied were Ponte Nova and Bariri , both resulting from dams on Tietê River. Sampling was carried out as a screening of the system in 90 sampling station in each reservoir. Sampling were carried out in four periods: January, April, July and October 2001. Both reservoirs are polimictic and had an anoxic hypolimnium in January. The concentrations of nitrogen and phosphourus compounds as well as chlorophyll a indicated that Ponte Nova Reservoir is oligo-mesotropic whereas Bariri Reservoir is hipereutrophic. Benthic invertebrates were collected using a Van Veen grab (378cm²) and washed trough a sieve with 210 um open-aperture. A total of 36 were identified in Ponte Nova Reservoir and 39 in Bariri. They belonged to the Oders Ephemeroptera, Diptera, Odonata and Trichoptera (Class Insecta), besides representatives of Oligochaeta and Hirudinea Classes (Filo Anellida) and Gastropoda and Bivalvia Classes (Filo Mollusca). In Ponte Nova Reservoir the highest richness was found in the family Chironomidae (Diptera) represented by 21 taxa, followed by Oligochaeta with 10 species. On the other hand, in Bariri Reservoir Oligochaeta was the group with highest the richness represented by 16 species, followed by Chironomidae with 13 taxa. Chaoborus (Diptera) was numerically dominat in the bentic macroinvertebrate community of Ponte Nova reservoir. They correspond to 77% of the sampled organisms. In Bariri Reservoir, Branchiura sowerbyi (Oligochaeta) was the dominat organism corresponding to 47,6%. During the study period the highest densities of macroinvertebrates were found in Bariri reservoir varying between 1024.1 and 1657.0 ind.m-2, compared with 562 e 850.0 ind.m-2 in Ponte Nova. The analysis of distribuition of organisms in relation to depth showed that Chaoborus inhabited preferentially the deep region in both reservoirs, whereas Chironomidae and Mollusca, preferred the littoral region. For Oligocheta it was observed that in Ponte Nova Reservoir this group preferentially occupied shallow areas, whereas in Bariri the highest densities were found in the deepest zone. An analysis of Shannon-Wiener diversity index and the relation Oligochaeta/Chironamidae showed that the latter was best in characterizing the tropic state of studied environments.